Metabolism of heme and bilirubin in rat and human small intestinal mucosa. - Hartmann, F (1982)
Formation of heme, bilirubin, and bilirubin conjugates has been examined in mucosal cells isolated from the rat upper small intestine. Intact, viable cells were prepared by enzymatic dissociation using a combined vascular and luminal perfusion and incubated with an isotopically labeled precursor, delta-amino-[2,3-3H]levulinic acid. Labeled heme and bile pigment were formed with kinetics similar to those exhibited by hepatocytes. Moreover, the newly formed bilirubin was converted rapidly to both mono- and diglucuronide conjugates. In addition, cell-free extracts of small intestinal mucosa from rats or humans exhibited a bilirubin-UDP-glucuronyl transferase activity that was qualitatively similar to that present in liver. The data suggest that the small intestinal mucosa normally contributes to bilirubin metabolism.